Investigating the Effect of Copper Sulphate on Hydrogen Peroxide Bleaching with Hydrolysis on P/C Fabric Mechanical Properties - Hayavadana, J.; Samatha, K. (New Approaches in Engineering Research Vol. 12, 2021)
Polyester is known for its hydrophobicity and efforts are being made to improve the same. In this research work laboratory woven 67/33 polyester / cotton suiting material is treated with cupper sulphate and hydrogen peroxide bleaching followed by oxidation deweighting process to improve all its mechanical and comfort properties including hydophilicity.The experimental methodology included selection of 3 levels of copper sulphate, two levels of Material to liquor ratio, two levels of temperature and a constant level of sodium hydroxide. In all the cases samples were treated in HTHP beaker dyeing machine followed by standard after treatment procedures. The treated samples were characterized for various properties .It was found that the experimental parameters like concentration of copper sulphate, alkaline oxidation deweighting process had significant effects as shown by interesting results like improvement of compressibility, crease recovery angle, bending length and with acceptable loss of tensile strength.